Interior Griya Lanjut Usia St.Yosef di Jawa Tengah - Lucky Basuki, Angeli Kosasih Laksmi Kusuma Wardani (Intra, 2014)
Elderly house is a building that functioned as a shelter for the elderly man was being treated, cared for and given more attention. Numbers of elderly who do not consider the functional aspects and comfort make the elderly are reluctant to stay in elderly house. The purpose of this scheme is to provide seniors with atmosphere and design of the natural environment, safe, back to nature for the elderly and provide full facilities to serve the needs of the elderly. The concept of this design is applied to the familiarity of the layout, organization of space and furniture and adjacent groups. In addition, the combination of colors and materials also supports the concept of familiarity on St.Yosef elderly house. In St. Yosef between public spaces interconnected set, used together, and open to one another, this interior design benefits the elderly is to provide a means for the elderly where they can socialize with comfortable quarters feel feel like home.